Effect of cooking brassica vegetables on the subsequent hydrolysis and metabolic fate of glucosinolates - Rungapamestry, Vanessa; Duncan, Alan J.; Fuller, Zoë; Ratcliffe, Brian (Proceedings of the Nutrition Society, 2007)
The protective effects of brassica vegetables against cancer may be partly related to their glucosinolate content. Glucosinolates are hydrolysed by plant myrosinase following damage of plant tissue. Isothiocyanates are one of the main groups of metabolites of glucosinolates and are implicated in the preventive effect against cancer. During cooking of brassica the glucosinolate–myrosinase system may be modified as a result of inactivation of plant myrosinase, loss of enzymic cofactors such as epithiospecifier protein, thermal breakdown and/or leaching of glucosinolates and their metabolites or volatilisation of metabolites. Cooking brassica affects the site of release of breakdown products of glucosinolates, which is the upper gastrointestinal tract following consumption of raw brassica containing active plant myrosinase. After consumption of cooked brassica devoid of plant myrosinase glucosinolates are hydrolysed in the colon under the action of the resident microflora. Feeding trials with human subjects have shown that hydrolysis of glucosinolates and absorption of isothiocyanates are greater following ingestion of raw brassica with active plant myrosinase than after consumption of the cooked plant with denatured myrosinase. The digestive fate of glucosinolates may be further influenced by the extent of cell rupture during ingestion, gastrointestinal transit time, meal composition, individual genotype and differences in colonic microflora. These sources of variation may partly explain the weak epidemiological evidence relating consumption of brassica to prevention against cancer. An understanding of the biochemical changes occurring during cooking and ingestion of brassica may help in the design of more robust epidemiological studies to better evaluate the protective effects of brassica against cancer.